Integrated Georeferencing of LiDAR and Camera Data Acquired from a Moving Platform - F. Liebold; H.-G. Maas (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2014)
This paper presents an approach for modeling the trajectory of a moving platform equipped with a laser scanner and a camera. In most cases, GNSS and INS is used to determine the orientation of the platform, but sometimes it is impossible to use GNSS, especially indoor applications should be mentioned here. INS has a bad error propagation without GNSS. In addition, the accuracy of GNSS and low-cost INS is limited and often not equivalent to the accuracy potential of laser scanners. For the camera, there exists the well-known alternative to obtain the orientation parameters via triangulation, for instance employing structure-from-motion techniques. But it is more challenging to find an alternative for the laser scanner, because of its sequential data acquisition. In the approach shown here, we propose to use a camera in combination with structure-from-motion techniques as the basis for determining the laser scanner trajectory parameters. For that purpose, we use piece-wise models for the trajectory through polynomial functions, supported by time-stamped matches between laser scanner and camera data.